Coordinated Control Strategies for Offshore Wind Farm Integration via VSC-HVDC for System Frequency Support - Yujun Li; Zhao Xu; Ostergaard, Jacob; Hill, David J. (IEEE transactions on energy conversion, 2017)
Coordinated control strategies to provide system inertia support for main grid from offshore wind farm that is integrated through HVdc transmission is the subject matter of this paper. The strategy that seeks to provide inertia support to the main grid through simultaneous utilization of HVdc capacitors energy, and wind turbines (WTs) inertia without installing the remote communication of two HVdc terminals is introduced in details. Consequently, a novel strategy is proposed to improve system inertia through sequentially exerting dc capacitors energy and then WTs inertia via a cascading control scheme. Both strategies can effectively provide inertia support while the second one minimizes the control impacts on harvesting wind energy with the aid of communication between onshore and offshore ac grids. Case studies of a wind farm connecting with a HVdc system considering sudden load variations have been successfully conducted to compare and demonstrate the effectiveness of the control strategies in DIgSILENT/PowerFactory.